Peningkatan Produktivitas Tanaman Kangkung Darat (Ipomoea reptans Poir.) Melalui Pemberian Macam Pupuk Organik Cair - Asan Susanto; Choirul Anam; Dian Eka Kusumawati (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2025)
Land kale is a fast-growing cultivated crop with relatively affordable prices in various audiences. In Indonesia, the production of kale increases from year to year along with the need for consumption of kale vegetables by the community. The increasing public awareness of the importance of body health, demands to buy organic kale vegetable products that are free from chemicals. To increase the productivity of land kale plants can be practiced in various ways, namely by applying liquid organic fertilizer (POC) with the appropriate dose, method, and type. Aiming to understand the results of applying various liquid organic fertilizers on the productivity of land kale plants. This analysis applies a one-factor Randomized Group Design method with six levels with four repetitions. The factor is the type of liquid organic fertilizer including: POC Nasa, Multitonic, Infarm, KNO3, Agroflangi, and BIO NPK+Ga3+ HUMIT ACID. The widest leaf width, long plant height, longest leaf, number of leaves, and total plant fresh weight were the parameters observed. The results of the observations were tested with Fisher level 5 & 1%, if there was a significant difference, the 5% BNT test was continued. The results showed that the provision of POC KNO3 gave the best results among other types of POC on the productivity of ground kale.